A1. Annex 15: Notification proposing to revoke and modify existing General Conditions and set new General Conditions : Notification of Ofcom’s proposals to revoke and modify existingGeneral Conditions and set new General Conditions under sections48(1) and 48A(3) of the Communications Act 2003.: Notification of Ofcom’s proposals to revoke and modify existingGeneral Conditions and set new General Conditions under sections48(1) and 48A(3) of the Communications Act 2003. ([2020]) - Unknown
No abstract available